Manfaat Saffron dalam Meringankan Sindrom Pramenstruasi - Nur Setiawati Rahayu; Debby Endayani Safitri (JURNAL KESEHATAN REPRODUKSI, 2021)
Background: Menstrual disorders are experienced by most women of reproductive age, this problem if not handled seriously will have an adverse impact. Most women choose to treat menstrual disorders with medical treatment without knowing the side effects of using these drugs.Objective: This study aims to find solutions or alternative in dealing with Premenstrual syndrom other than by medical treatment.Methods: This study uses a systematic review method, where this study examines and integrates findings from published studies to draw conclusions.Results and Discussion: The results of this study indicate that saffron is effective in helping to reduce the severity and reduce the duration of menstrual disorders. Such as anxiety, depression, pain and other disorders.Conclusion: Consumption 30mg of saffron per-day can be useful reducing symptoms of menstrual disorder like depression, pain and hormonal balance.   Keywords: Menstrual Disorder, Saffron, Systematic Review